What's In a Name? Name Giving, Identity, and Script Formation. (July 2015) - Jagieła, Jarosław; Gębuś, Dorota
This article deals with the significance of a person's name in relation to his or her life script and is focused specifically on Polish culture and context. A survey of 90 university students ages 21-23 revealed that most of them believe that their names were chosen in a purposeful manner, and they have a positive attitude toward those names. The findings also indicated that when survey participants were addressed by their parents, mothers used diminutives more often than fathers. In choosing their child's first name, most parents wanted it to sound nice and be original, whereas the second name was often the same as that of an important family member. Interviews conducted with several students confirmed the existence of a link between names and various aspects of life script.